An Unforgettable Dalit Voice : Life, Writings and Speeches of M.C. Rajah - Basu, Swaraj, (Brill | Manohar Publishers & Distributors, 2024)
This book is a collection of writings and speeches of M.C. Rajah, who was one of the great Dalit leaders of pre-lndependent India. Anyone interested in understanding the history of India's Dalit movement will find this book very valuable. M.C. Rajah was born in a Dalit family of Tamil Nadu in 1883 and till he died in 1943 he was in the forefront of the Dalit's struggle for equality, justice and rights. What is most important about him is that he was the first Dalit leader in the Madras Legislative Council and also the first Dalit leader in the Central Legislative Assembly. His commitment towards the cause of Dalits and particularly his efforts to make provision for education of Dalits drew the attention of the British government and he was conferred the title of Rai Bahadur in 1922. Being influenced by the Non-Brahmin movement in Tamil Nadu M.C. Rajah realized the importance of mobilizing Dalits whose interests in his opinion were not protected by Non-Brahmin leaders. Written in 1925 his book, The Oppressed Hindus , gives an account of the glorious history and tradition of Dalits in Tamil Nadu and the new identity given to them as 'Adi-Dravidas'. M.C. Rajah's representations to the British government, correspondence with Gandhiji and Dr. B.R. Ambedkar and his speeches in the provincial and central legislatures for about twenty years provide valuable insights about his struggle for the empowerment of Dalits.